Looking Backwards and Forwards: Gainers and Losers in Tanzania ' s Primary Education System - Komba, Aneth (Papers in Education and Development, 2018)
This paper takes a historical view to examine the primary education system on Tanzania Mainland with a view to highlighting the gainers from and losers in this system. The paper will first provide a contextual analysis of Tanzania ' s primary education system. In this process, the paper examines the key foundational principles that have shaped the education system in Tanzania from the colonial to the post-colonial period and it highlights the educational policies aimed at encouraging children ' s engagement with primary schooling. The paper further examines what seems to have worked or not worked in ensuring access to quality education by all. In the second part of the presentation, the paper examines the losers and gainers from the current primary education system. Finally, the paper makes a projection of the way forward before the concluding remarks are presented.